Genome-Scale CRISPR Screening Reveals Host Factors Required for Ribosome Formation and Viral Replication - Maikke B. Ohlson; Jennifer L. Eitson; Alexandra I. Wells; Ashwani Kumar; Seoyeon Jang; Chunyang Ni; Chao Xing; Michael Buszczak; John W. Schoggins (mBio, 2023)
ABSTRACT Viruses are known to co-opt host machinery for translation initiation, but less is known about which host factors are required for the formation of ribosomes used to synthesize viral proteins. Using a loss-of-function CRISPR screen, we show that synthesis of a flavivirus-encoded fluorescent reporter depends on multiple host factors, including several 60S ribosome biogenesis proteins. Viral phenotyping revealed that two of these factors, SBDS, a known ribosome biogenesis factor, and the relatively uncharacterized protein SPATA5, were broadly required for replication of flaviviruses, coronaviruses, alphaviruses, paramyxoviruses, an enterovirus, and a poxvirus. Mechanistic studies revealed that loss of SPATA5 caused defects in rRNA processing and ribosome assembly, suggesting that this human protein may be a functional ortholog of yeast Drg1. These studies implicate specific ribosome biogenesis proteins as viral host dependency factors that are required for synthesis of virally encoded protein and accordingly, optimal viral replication. IMPORTANCE Viruses are well known for their ability to co-opt host ribosomes to synthesize viral proteins. The specific factors involved in translation of viral RNAs are not fully described. In this study, we implemented a unique genome-scale CRISPR screen to identify previously uncharacterized host factors that are important for the synthesis of virally encoded protein. We found that multiple genes involved in 60S ribosome biogenesis were required for viral RNA translation. Loss of these factors severely impaired viral replication. Mechanistic studies on the AAA ATPase SPATA5 indicate that this host factor is required for a late step in ribosome formation. These findings reveal insight into the identity and function of specific ribosome biogenesis proteins that are critical for viral infections.